DEVELOPING PROFESSIONAL FOREIGN LANGUAGE COMPETENCE OF MEDICAL STUDENTS THROUGH EMI TECHNOLOGIES - G. A. Meliqo‘ziyeva (Modern American Journals, 2025)
This scientific article comprehensively investigates the theoretical foundations, methodological approaches, and practical effectiveness of developing professional English language competence among medical students using English as a Medium of Instruction (EMI) technologies in the modern educational process. The study analyzes the impact of various EMI technological tools on mastering medical terminology, developing clinical communication skills, improving the ability to work with scientific literature, and preparing for international collaborative activities. The results demonstrate that an integrated EMI-based approach significantly enhances not only students' language skills but also their overall professional competencies, transforming them into competitive specialists capable of meeting the demands of the globalization era.
Keywords: EMI, medical education, professional foreign language competence, technological integration, virtual reality, language learning platforms, telemedicine, medical terminology.